Estudo da expressão imuno-histoquímica das MMPs -2, -7, -9 e -26 e TIMPs -1 e -2 em adenomas pleomórficos e carcinomas adenóides císticos de glândulas salivares menores - Freitas, Valéria Souza (2011)
The balance between the expression of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) has been related to various physiological and pathological processes, including salivary gland morphogenesis and tumor invasion and metastasis processes. Pleomorphic adenoma (PA) and adenoid cystic carcinoma (ACC) respectively represent benign and malignant neoplasias of salivary glands. Although they share the same cell origin, they present distinct biological behavior. The aim of this study was to compare the immunohistochemical expression of MMPs -2, -7, -9 and -26, and of TIMPs -1 and -2, in cases of PA and ACC of minor salivary glands. Twenty cases of PA and twenty cases of ACC were assessed according to the presence, intensity and location of MMPs and TIMPs in the tumor parenchyma. Most of the PAs and ACCs presented a high expression of MMP -2, -7, -9 and -26 and of TIMP -1 and -2, predominantly located in tumor cells. There was no significant difference in the expression of MMPs -2 (p=0.359), -7 (p=0.081) and -26 (p=0.553), as well as of TIMPs -1 (p=0.657) and -2 (p=0.248), between the parenchyma of PAs and ACCs. However, MMP-9 showed a significant difference of expression between the two tumors, with the ACC showing more intense marking for this gelatinase (p=0.041). The strong expression of MMP-9 observed in the parenchyma suggests that this gelatinase may play an important role in the biological behavior of these tumors. On the other hand, although there was no significant difference between the marking of MMP -2, 7 and 26 in the studied tumors, the data, when analyzed as a whole, suggest that these proteases may take part in the process of tissue remodeling in both tumors, but do not present a direct relation with the pattern of aggressiveness of ACC. Nonetheless, matrilisins may indirectly influence the behavior of this tumor due to their capacity of activating MMP-9, strongly expressed in the parenchyma of ACC